The Effect of Budgetary Participation, Public Accountability and Decentralization on Managerial Performance with Organizational Commitment as a Moderating Variable (a Study on Regional Apparatus Organizations on Sungai Penuh City) - Edo Agus Pratama; Yudi; Ratih Kusumastuti (Citakonsultindo, 2025)
Managerial performance in public sector organizations is an important aspect in realizing effective, efficient, and accountable governance. However, various phenomena in the Regional Apparatus Organizations (OPD) of Sungai Penuh City indicate a discrepancy between the set performance targets and the achieved results, low quality of budget implementation, variations in the implementation of public accountability, and asynchronous implementation of decentralization of authority between work units. These conditions indicate the need for an evaluation of the factors that influence managerial performance. This study aims to analyze the effect of budget participation, public accountability, and decentralization on managerial performance, and to examine the role of organizational commitment as a moderating variable in OPDs of Sungai Penuh City. The study used a quantitative approach with a survey technique through the distribution of questionnaires to structural officials of echelon III and IV across all OPDs of Sungai Penuh City. The sample was determined by the purposive sampling method with 160 respondents. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach through SmartPLS 4.0 which includes evaluation of the outer model, inner model, and testing of moderation effects. The results of the study indicate that budget participation has a significant effect on managerial performance, public accountability has an effect on managerial performance, and decentralization has also been shown to have an effect on managerial performance. However, organizational commitment does not moderate the effect of budget participation on managerial performance and does not moderate the effect of decentralization on managerial performance. Conversely, organizational commitment has been shown to moderate the effect of public accountability on managerial performance. The findings of this study provide important implications for local governments, namely that strengthening manager1ial performance does not only need to focus on increasing budget participation, accountability quality, and decentralization effectiveness, but also requires selective strengthening of organizational commitment aspects, especially in the context of public accountability. This study is expected to contribute to the development of public sector management literature and serve as a reference for local governments in formulating policies to improve managerial performance.